Quality of Drinking Water in the Rural Peripheral Areas of Quevedo Canton, Ecuador (TERRA LATINOAMERICANA, 2025)
The quality of drinking water is a crucial aspect for the health and well-being of any community, especially in the rural peripheral areas of Quevedo canton, Ecuador, where the drinking water supply infrastructure is deficient and exposure to contaminants is high. In our study we aim to conduct a comprehensive analysis of drinking water quality. Five representative localities in Quevedo canton were selected for the evaluation of microbial load and analysis of total coliforms, soil texture, soil pH, and the content of nitrates, nitrites, copper, and chromium in the water. Our results showed significant variations in water and soil quality among the localities. The microbial load and total coliform counts were highest in SCR 3, indicating a possible local contamination source. The soil texture varied, with a predominance of sandy texture in SCR 2 and SCR 3, which af fects water retention and nutrient availability.Soil pH values ranged from 6.0 to 7.0, with SCR 3 presenting the lowest pH. Nitrate concentration was highest in SCR 2 (20 mg L-1), while nitrites were highest in ESP 2 (0.12 mg L-1). Copper levels varied, being highest in AGR (18 mg L-1), lastly, hexavalent chromium levels were highest in SCR 2 (0.075 mg L-1). These variations in water and soil quality have significant implications for public health and agricultural productivity. Sources of contamination were identified in our study, hence, we propose mitigation measures to improve water quality, promote public health, and support sustainable agricultural development in the rural communities of Quevedo.
Keywords: contamination; chromium; localities; nitrates; public health